Understanding the factors influencing biosecurity adoption on smallholder poultry farms in Ghana: a qualitative analysis using the COM-B model and Theoretical Domains Framework - Anica Buckel; Anica Buckel; Kofi Afakye; Eric Koka; Cortney Price; Emmanuel Kabali; Mark A. Caudell (Frontiers in Veterinary Science, 2024)
IntroductionAntimicrobial resistance (AMR) poses a significant global threat to public, animal, and environmental health, consequently producing downstream economic impacts. While top-down approaches to addressing AMR (e.g., laws regulating antimicrobial use) are common in high-income countries, limited enforcement capacities in low- and middle-income countries highlight the need for more bottom-up approaches. Within agriculture, efforts to apply bottom-up approaches to AMR have often focused on the promotion of biosecurity, which should reduce the need for antimicrobials by mitigating disease risk and limiting AMR transmission. Traditionally, efforts to encourage biosecurity adoption have emphasized training and awareness-raising initiatives. However, a growing body of research suggests a disconnect between knowledge and behavior, highlighting the existence of a knowledge–action gap.MethodTo understand the barriers and enablers patterning the knowledge-action gap in on-farm biosecurity uptake, we draw upon models from behavioral science. We analyzed in-depth interviews and two focus group discussions with smallholder poultry producers in Ghana to understand factors underlying the intention–action gap in adopting biosecurity. As an analytical framework, we draw upon the Theoretical Domains Framework in combination with the Capability-Opportunity-Motivation Behavioral Model.Results and discussionWhile smallholder poultry farmers in Ghana were aware of the importance of biosecurity practices, they struggled with consistent implementation. Financial constraints, challenges in adapting practices to the local context, and limited resources hindered adoption. Additionally, cognitive biases like prioritizing short-term gains and underestimating disease risks played a role. However, some farmers found motivation in professional identity and social influences. These findings highlight the need for designing biosecurity interventions that consider human behavioral factors and the context in which behavior occurs. This underscores the importance of collaboration across disciplines, including veterinary science and the social and behavioral sciences. Implications and recommendations for researchers and practitioners are discussed.